2018
DOI: 10.3390/ijms19113429
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Immunomodulatory Protein from Nectria haematococca Suppresses Growth of Human Lung Adenocarcinoma by Inhibiting the PI3K/Akt Pathway

Abstract: Lung cancer is a common disease that is associated with poor prognosis. Fungal immunomodulatory protein from Nectria haematococca (FIP-nha) has potential as a lung cancer therapeutic; as such, illuminating its anti-tumor mechanism is expected to facilitate novel treatment options. Here, we showed that FIP-nha affects lung adenocarcinoma growth ex vivo and in vivo. Comparative quantitative proteomics showed that FIP-nha negatively regulates PI3K/Akt signaling and induces cell cycle arrest, autophagy, and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…In early studies, we confirmed that FIP-nha induced A549 cell apoptosis by negatively regulating PI3K/Akt signaling using comparative quantitative proteomics [20]. Because of the complexities of antitumor effects and crosstalk among anti-tumor pathways, 1 H NMR-based metabolomics was applied to investigate A549 cell metabolic signatures after rFIP-nha treatment with the aim of comprehensively understanding the underlying mechanisms and assessing the diagnostic potential of this protein.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In early studies, we confirmed that FIP-nha induced A549 cell apoptosis by negatively regulating PI3K/Akt signaling using comparative quantitative proteomics [20]. Because of the complexities of antitumor effects and crosstalk among anti-tumor pathways, 1 H NMR-based metabolomics was applied to investigate A549 cell metabolic signatures after rFIP-nha treatment with the aim of comprehensively understanding the underlying mechanisms and assessing the diagnostic potential of this protein.…”
Section: Discussionmentioning
confidence: 91%
“…at 8 μg/mL show obvious anti-tumor activity towards human tumor cells [21,26], but FIP-fve did not show anti-tumor activity until the concentration reached 195 μg/mL [22]. In addition to the above FIPs, five other FIPs with excellent direct anti-tumor effects have been identified by our laboratory using genetic engineering methods [20,27,28,29]. Among them, FIP-nha showed the strongest and broad-spectrum anti-tumor activities, and could induce A549 cell apoptosis by G1/S arrest [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a precise mechanism is still unknown, there are relevant illustrations of some structural-related bioactive functions. For instance, FIP-gts ( 124 ), FIP-nha ( 125 ), and LZ-8 ( 126 ) can be transported into tumor cells and exert toxicity, and LZ-8 could even enter the nucleus of NB4 cells ( 127 ). The way they distinguish tumor cells and normal cells, the vital structure which enters the cell and behaves toxically, and the mechanism of their anti-tumor activity need further investigation.…”
Section: Prospectsmentioning
confidence: 99%